Phonological Processes in A 18-Months Bilingual Toddler - Agung Setiyono; Lia Maulia Indrayani; Ypsi Soeria Soemantri (Lecturer Association of Linguistics, Language Teaching, and Literature Studies in Indonesi, 2020)
The toddler’s first words were unintelligible speech by adult. This study was conducted to investigate the language development undergone by a 18-months bilingual toddler. The study of language development had two perspectives in terms of clinical and linguistic perspective. This study was a linguistic perspective to find out the language development processes especially in phonological processes undergone by a 18-months bilingual toddler. This study employed descriptive case study as the method with observation and video recording as the data collection. The participant of this study was a 18-months Javanesse-Indonesian toddler. The data were collected for 30 days. The data were categorized and analyzed based on Ingram's theory (1976). The result revealed that there were three categories of phonological processes undergone by 18-months Javanesse-Indonesian toddler such as substitution, assimilatory, and syllable structure processes. The syllable structure processes with initial consonant deletion is the most dominant types of phonological processes. The results are expected to enrich the study of language development especially in a 18-months Javanesse-Indonesian toddler in which the information will benefit for the practicing clinicians.